Efektivitas Penggunaan Mendeley dalam Penyusunan Skripsi oleh Mahasiswa Program Studi Pendidikan Bahasa Indonesia Periode Juli–Desember 2025 - Putri, Theodelind Eunike Pramesti Dawa; Hariadi, Try (Indonesian Journal of Teaching and Teacher Education, 2025)
This study aims to examine the effectiveness of using Mendeley in supporting thesis writing, particularly in citation and bibliography preparation among Indonesian Language Education students. This research employed a descriptive qualitative approach involving students who actively used Mendeley during the thesis-writing process. Data were collected through open-ended questionnaires distributed via Google Forms and supported by documentation in the form of screenshots of citations and bibliographies generated using Mendeley. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that the use of Mendeley is effective in assisting thesis writing. Mendeley helps students improve ease of use, increase time efficiency in writing citations and bibliographies, maintain consistency of citation formats, and manage references more systematically. However, several technical challenges were identified, such as incomplete metadata and synchronization issues, which require manual verification by users. Overall, Mendeley is considered an effective reference management tool in supporting the technical aspects of academic writing when accompanied by adequate user understanding.